Early addition of rituximab in the management of myositis associated with systemic lupus erythematosus - Mervat E Behiry; Ahmed Shaker; Kyrillus Shohdy; Fadi Nagy (SpringerOpen, 2019)
Targeting B-cell in systemic lupus erythematosus (SLE) seems to be a promising approach. Although rituximab failed to show efficacy in refractory SLE in clinical trial setting, real-world experience still shows some efficacy in certain situations. A 20-year-old woman was diagnosed with SLE with coexistent myositis. The patient's muscular condition did not improve on corticosteroids, addition of rituximab could achieve complete response. Introducing rituximab early for the nonrenal manifestations of SLE merits further investigation.